Characterization of Deltacoronavirus in Black-Headed Gulls (Chroicocephalus ridibundus) in South China Indicating Frequent Interspecies Transmission of the Virus in Birds - Chu, Kan-Kan; Zhou, Zhi-Jian; Wang, Qiong; Ye, Sheng-Bao; Guo, Ling; Qiu, Ye; Zhang, Yun-Zhi; Ge, Xing-Yi (Frontiers in Microbiology, 2022)
Deltacoronavirus (DCoV) is a genus of coronavirus (CoV) commonly found in avian and swine, but some DCoVs are capable of infecting humans, which causes the concern about interspecies transmission of DCoVs. Thus, monitoring the existence of DCoVs in animals near communities is of great importance for epidemic prevention. Black-headed gulls (Chroicocephalus ridibundus) are common migratory birds inhabiting in most urban and rural wetlands of Yunnan Province, China, where is a typical habitat for black-headed gulls to overwinter. Whether Yunnan black-headed gulls carry CoV has never been determined. In this study, we identified three strains of DCoVs in fecal samples of Yunnan black-headed gulls by reverse-transcriptional PCR and sequenced their whole genomes. Genomic analysis revealed that these three strains shared genomic identity of more than 99%, thus named as DCoV HNU4-1, HNU4-2 and HNU4-3; their NSP12 showed high similarity of amino acid sequence to the homologues of falcon coronavirus UAE-HKU27 (HKU27), houbara coronavirus UAE-HKU28 (HKU28) and pigeon coronavirus UAE-HKU29 (HKU29). Since both HKU28 and HKU29 were found in Dubai, there might be cross-border transmission of these avian DCoVs through specific routes. Further coevolutionary analysis supported this speculation that HNU4 (or its ancestors) in black-headed gulls originated from HKU28 (or its homologous strain) in houbara, which was interspecies transmission between two different avian orders. In addition, interspecies transmission of DCoV from houbara to falcon, pigeon and white-eye, from sparrow to common-magpie, quail and mammal including porcine and asian leopard cat, from munia to magpie-robin were predicted. This is the first report of black-headed gull DCoV in Asia which was highly homologue to other avian DCoVs, and the very “active” host switching events in DCoV were predicted, which provides important reference for the study of spread and transmission of DCoVs.